What are the respiratory health research priorities in Alberta, Canada? A stakeholder consultation - Michael K Stickland; Sachin R Pendharkar; Jananee Rasiah; Joanna E MacLean; Heather Sharpe; Lisa Cerato; Darlene Derech; Lisa Guirguis; Kathleen Hayward; Tara Lohmann; Elizabeth Manafo; Janice Paskey; et al. (BMJ Open)
Objective The Respiratory Health Strategic Clinical Network (RHSCN) was launched to facilitate respiratory and sleep health through implementation of innovative, patient-centred, evidence-informed coordinated services in Alberta. In collaboration with project partners, the RHSCN aimed to determine the respiratory research priorities for Alberta.Design The four phases of this research prioritisation project were (1) identifying research questions from stakeholders, (2) determining which research questions had been answered in existing literature, (3) prioritising unanswered questions and (4) finalising the priorities through an inperson workshop.Setting The study occurred in Alberta, Canada over a 2-year period beginning in March 2017.Participants A total of 448 patients, clinicians and other stakeholders consented to participate in the survey.Results A total of 595 possible questions were submitted, with 343 unique questions identified. Of the questions, 94 were out of scope, 155 answered by existing literature and 10 were combined with others, while 83 were determined to be unanswered in the literature. Stakeholders were surveyed again to prioritise the remaining 83 questions and they were reviewed by the project’s Steering Committee (clinicians and patients). At the inperson workshop, the Steering Committee identified 17 research topics as priority areas for respiratory and sleep research in Alberta.Conclusion A stakeholder-led research prioritisation process identified optimal clinical management/follow-up, equitable access to services, and management of social, psychological and mental health issues related to respiratory/sleep health as priority research areas.